A Transatlantic Transfer of Cultural Values: Constructing A Canada-Related Cultural Reader Series for the Secondary English Classroom in Central Europe - Bánhegyi, Mátyás; Nagy, Judit (Review of International American Studies, 2014)
Mátyás Bánhegyi and Judit Nagy Department of English Linguistics Károli Gáspár University of the Reformed Church in Hungary Faculty of Humanities The ‘Canada in the English Classroom’ joint research team of the University of Colongne and Károli Gáspár University of the Hungarian Reformed Church has been producing a cultural reader series to enhance the dissemination of up-to-date and engaging cultural information on Canada through general English language classes for the secondary school age group in Central Europe. The cultural reader series is seen as a means of facilitating cultural discourse and cross-cultural learning, also advocated in Canadian contexts by Berrell and Gloet (1999). Using Kramsch’s (1991) and Damen’s (2003) theories, the readers have been devised so that more abstract and/or lesser-known Canadian cultural aspects can be brought closer to the target group through English as a foreign language. To realize this objective in an effective way in the English classroom, Gochenour and Janeway’s (1993) model of culture learning has been observed, which advocates the gradual involvement of students in culture-related issues: starting from observation of culture moving towards genuine communication about culture. After introducing the cultural reader series project briefly, the paper will discuss the theoretical background behind the series and the project activities leading up to the preparation and compilation of its completed volumes. As a next step, an overview of the content of these volumes and the accompanying teacher’s notes will be presented. This will be followed by a sample unit demonstration of how the series achieves the goals the research has targeted.